Protein Kinase Cε, Which Is Linked to Ultraviolet Radiation-Induced Development of Squamous Cell Carcinomas, Stimulates Rapid Turnover of Adult Hair Follicle Stem Cells - Ashok Singh; Anupama Singh; Jordan M. Sand; Erika Heninger; Bilal Bin Hafeez; Ajit K. Verma (Journal of Skin Cancer)
To find clues about the mechanism by which kinase C epsilon (PKCε) may impart susceptibility to ultraviolet radiation (UVR)-induced development of cutaneous squamous cell carcinomas (SCC), we compared PKCε transgenic (TG) mice and their wild-type (WT) littermates for (1) the effects of UVR exposures on percent of putative hair follicle stem cells (HSCs) and (2) HSCs proliferation. The percent of double HSCs (CD34+ and α6-integrin or CD34+/CD49f+) in the isolated keratinocytes were determined by flow cytometric analysis. Both single and chronic UVR treatments (1.8 kJ/m2) resulted in an increase in the frequency of double positive HSCs in PKCε TG mice as compared to their WT littermates. To determine the rate of proliferation of bulge region stem cells, a 5-bromo-2′-deoxyuridine labeling (BrdU) experiment was performed. In the WT mice, the percent of double positive HSCs retaining BrdU label was 28.4±0.6% compared to 4.0±0.06% for the TG mice, an approximately 7-fold decrease. A comparison of gene expression profiles of FACS sorted double positive HSCs showed increased expression of Pes1, Rad21, Tfdp1 and Cks1b genes in TG mice compared to WT mice. Also, PKCε over expression in mice increased the clonogenicity of isolated keratinocytes, a property commonly ascribed to stem cells.